Pengaruh Model Project Based Learning Berbantuan Media Autentik Terhadap Keterampilan Menulis Teks Berita Siswa Kelas XIi SMA Negeri 5 Merangin - Karina, Leni; Ulya, Ridha Hasnul; Tamsin, Andria Catri; Hafrison, Hafrison (Universitas Pakuan, 2026)
THE EFFECT OF THE PROJECT BASED LEARNING MODEL ASSISTED BY AUTHENTIC MEDIA ON THE NEWS TEXT WRITING SKILLS OF GRADE XI STUDENTS OF STATE HIGH SCHOOL 5 MERANGIN This study aims to describe the news text writing skills of class XI students of SMA Negeri 5 Merangin before and after the implementation of the Project Based Learning model assisted by authentic media and analyze the effect of its implementation on improving news text writing skills. This type of research is quantitative research with an experimental method using a one group pretest-posttest design. The study population was all class XI students of SMA Negeri 5 Merangin in the 2025/2026 academic year, totaling 192 students, while the study sample was 32 class XI F6 students selected using a purposive sampling technique. The research instrument was a performance test of news text writing skills assessed based on indicators of news text structure, completeness of 5W + 1H elements, and reading journalistic language and EYD. The results showed that the average value of students' text writing skills before treatment was 55.53 with an Almost Sufficient qualification, while after treatment it increased to 78.51 with a Good qualification. The results of the t-test show that the calculated t_value > t_table (7.97 > 1.697) at a significance level of 0.05, so it can be concluded that the application of the Project Based Learning model assisted by authentic media has a significant effect on the news writing skills of class XI students of SMA Negeri 5 Merangin.